Improving Health Literacy Knowledge, Behaviors, and Confidence with Interactive Training - Cori Gibson; Danielle Smith; Andrea K. Morrison (SLACK Incorporated, 2022)
Background: Ensuring that health care professionals are knowledgeable about the influence limited health literacy has on health outcomes and how to apply health literate strategies is crucial to transform quality and safety in care settings. Although many organizational efforts to address health literacy have focused on hospital settings, few have focused on primary care. The designation of a patient-centered medical home requires the need to address integrating health literacy and the training needs of primary care settings. Brief description of activity: An interactive health literacy training intervention was developed, implemented, and evaluated for 25 primary care clinics. This included an online educational module, in-person application activities, and a sustainability plan to continue skill building, reinforce behaviors, and support practice. Implementation: Using a descriptive pre- and post-training design, three survey measures were used to rate health literacy knowledge, behaviors, and confidence levels of more than 475 primary care staff. A pre-training survey was completed prior to completion of an interactive online health literacy module and attendance at an in-person training session which followed. A post-training survey was then completed. Sustainment activities, including lunch and learns, and reinforcement activities by clinic leaders, were initiated to promote use of the strategies in practice. A 1-year follow-up survey was then administered to measure sustainability. Results: The interactive training intervention improved primary care staff's knowledge, behaviors, and confidence in using health literacy strategies with patients and families. Common barriers and facilitators around the use of these strategies were also identified. Lessons learned: Careful consideration should be taken when developing health literacy training to ensure it will be effective, efficient, and sustainable. Using elements that facilitate the transfer of training to practice will help improve success. Addressing barriers and promoting facilitators, as well as integrating and connecting health literacy strategies with existing organizational goals and initiatives offer additional ways to reinforce and sustain the practice change. [HLRP: Health Literacy Research and Practice. 2022;6(2):e113-e120.] Plain Language Summary: Clinic staff can improve how they provide information and education to children and families. Interactive training about health literacy led clinic staff to (1) know more about health literacy, (2) use health literacy strategies more, and (3) feel more confident using health literacy strategies. Training over time, supporting staff, and connecting to organizational goals are important for sustainment.